2021
DOI: 10.1111/jcmm.16440
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate sulfotransferase 3 (CHST3) overexpression promotes cartilage endplate‐derived stem cells (CESCs) to regulate molecular mechanisms related to repair of intervertebral disc degeneration by rat nucleus pulposus

Abstract: To investigate the regulatory effect of carbohydrate sulfotransferase 3 (CHST3) in cartilage endplate‐derived stem cells (CESCs) on the molecular mechanism of intervertebral disc degeneration after nucleus pulposus repair in rats. We performed GO and KEGG analysis of GSE15227 database to select the differential genes CHST3 and CSPG4 in grade Ⅱ, Ⅲ and Ⅳ intervertebral disc degeneration, IHC and WB to detect the protein profile of CHST3 and CSPG4, Co‐IP for the interaction between CHST3 and CSPG4. Then, immunofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…54,57,61,63,[68][69][70]76 Eight studies elaborated on the biological potential of CESCs in intervertebral disc regeneration. 55,67,[71][72][73][74][75]77…”
Section: Key Findings Of Cescsmentioning
confidence: 99%
See 2 more Smart Citations
“…54,57,61,63,[68][69][70]76 Eight studies elaborated on the biological potential of CESCs in intervertebral disc regeneration. 55,67,[71][72][73][74][75]77…”
Section: Key Findings Of Cescsmentioning
confidence: 99%
“…77 Similarly, Guan et al identified that overexpression of carbohydrate sulfotransferase 3 (CHST3) enhances the proliferation and migration capabilities of CESCs. 72 Insights gleaned from these studies offer a promising avenue for identifying potential molecular targets, which could inform the development of novel, more effective treatments for IDD. These advances in understanding the molecular dynamics of CESCs contribute significantly to the evolving landscape of IDD research, potentially leading to breakthroughs in regenerative medicine and therapeutics.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to providing topographic support and mechanical stimulus for cells, IVD grafts could also be loaded with bioactive agents ( Guan et al, 2021 ; Chen and Jiang, 2022 ). In order to achieve antioxidant properties in NP, Cheng et al fabricated an injectable thermosensitive hydrogel scaffold incorporated with ferulic acid as a controlled release system.…”
Section: Role Of Ivd Graft Substitutes In Stem Cell Microenvironmentmentioning
confidence: 99%
“…[5][6][7] Moreover, studies have shown that IVDD is not only caused by cell aging but also mainly because of the aging of adult stem cells that fail to timely replenish the aging and damaged cells in the tissues, suggesting that the CESCs in IVD may play an important role in IVDD. 8,9 Tension load (TL) contributes a lot to the initiation and progression of IVDD. 10,11 Therefore, the in-depth study of the specific mechanism of TL-induced CESCs degeneration is of great significance for the early prevention and treatment of IVDD.…”
Section: Introductionmentioning
confidence: 99%